THE EFFECT OF INTRA-ARTICULAR APPLICATION OF ALLOGENIC MESENCHYMAL STEM CELL COMBINE WITH VEGF TO GRAFT TUNNEL HEALING AND AUTOGRAFT TENDON INTEGRATION IN ACL RECONSTRUCTION; A BIOMECHANICAL STUDY - Ferdiansis, Ferdiansis (Journal of Stem Cell Research and Tissue Engineering, 2017)
Graft-tunnel healing is the most determination factors in successful of Anterior Cruciate Ligament (ACL) reconstruction. The application of bone marrow derived mesenchymal stem cell (MSC) and vascular endothelial growth factor (VEGF) are one of integration biological augmentation method that often used in ACL reconstruction. Combination intra-articular post ACL reconstruction  is expected to accelerate healing time and integration strength of tendon graft that used in bone tunnel. This method is experimental laboratory using animal model. The research is randomized post test only controlled group design. Five New Zealand white rabbit knee are used for ACL reconstruction with harmstring tendon graft and treated with combination allograft MSC and VEGF intra-articular, while five other rabbit knee as control without treatment. The evaluation is tensile test in third and six weeks post operation. Data was analyzed statistically and comparatively to compare the influence of MSC and VEGF to integration strength of graft tunnel healing. All the samples from treatment and control group found no complication after surgery. On third weeks evaluation, found a difference in failure tension load in both groups but not statistically significant (p>0,05), while on six weeks evaluation, found a statistically significant difference. Treatment group has a failure tension load higher than control group. While failure type of ACL tendon graft on 3 weeks evaluation, only 2 of 5 graft have pullout failure in treatment group. However, at three weeks in control group, the failure type of the tendon graft was a midsubtance rupture in intra-articular part during biomechanical tension test. The use of BM-MSC and VEGF intra-articular can increase tension failure load. It is expected that combination of BM-MSC and VEGF can increase integration process between bone graft and healing post ACL reconstruction, so that rehabilitation and mobilisation can be done earlier.Keywords: Graft-tunnel healing, ACL reconstruction, Vascular Endothelial Growth Factor (VEGF), Bone Marrow Derived Mesenchymal Stem Cell (BMMSC)